Exploring the diverse nanomaterials employed in dental prosthesis and implant techniques: An overview - Thirumalaivasan Natesan; Nangan Senthilkumar; Verma Deepak; Shellaiah Muthaiah; Ali Saheb; Rajendran Saravanan; Kanagaraj Kuppusamy; Pothu Ramyakrishna; Boddula Rajender; Radwan Ahmed Bahgat; Al-Qahtani Noora (Nanotechnology Reviews)
The landscape of prosthodontics and dental implantology is undergoing a transformative evolution, driven by remarkable advancements in materials science. This review explores the pivotal role of multifaceted materials, ceramics, polymers, metal alloys, and composites in revolutionizing dental restorative procedures. These materials are not only enhancing the mechanical properties and biocompatibility of dental prostheses and implants but also elevating aesthetic outcomes to meet patient expectations. Our discussion highlights how traditional materials like titanium (Ti) and cobalt-chromium (Co–Cr), alongside newer innovations such as zirconia and polymer-based composites, contribute to the restoration and enhancement of oral functions. Furthermore, this article delves into the integration of cutting-edge technologies such as 3D printing and computer-aided design/manufacturing, which synergize with these advanced materials to tailor dental solutions to individual patient needs, thereby improving both functional outcomes and patient satisfaction. As the field progresses, we anticipate future innovations to focus on increasing the sustainability of materials used, refining their properties through nanotechnology, and further personalizing dental care through digital workflows, setting a new standard in the interdisciplinary approach of modern dentistry.